Investigation of Chromosome Numbers and Plant Characteristics of Triticum compactum × Triticum turanicum Interspecific Hybrid in F2 Generation - Gülcan Eser; Oğuzhan Önal; Feyza Yıldırım; İmren Kutlu (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to identify the plants with varying chromosome numbers in the F2 generation, resulting from interspecific hybrids between hexaploid Triticum compactum and tetraploid Triticum turanicum, and to examine the morphological, physiological and agronomic characteristics of these plants. Therefore, the objective was to assess the potential for developing monosomic lines (particularly pentaploid) for the D-genome of wheat, with a view to their utilization in future breeding programs of wheat, and to ascertain the correlation between the estimated chromosome numbers and the superior phenotypic characteristics of the plants in question. The germination percentage was determined by germinating 230 seeds, which will form the F2 generation of Triticum compactum × Triticum turanicum interspecific hybrid, in Petri dishes together with the parents. Thereafter, the plants were transferred to 2 m long rows, 30 cm between rows and 10 cm above rows. The F2 plants were subjected to evaluation in order to ascertain their morphological, physiological and agronomic characteristics. Furthermore, the nuclear DNA contents of the F2 plants were determined by flow cytometry, and chromosome numbers were estimated based on the DNA contents of the parents. Finally, the correlations between the estimated chromosome numbers and the measured plant traits were determined. The nuclear DNA contents of F2 plants exhibited variability, with values ranging between 7870.39 and 11632.1 pg. Additionally, three plants with 35 chromosomes were identified. The F2 plants showed superior physiological traits compared to the parents, however, they displayed lower values for spike traits that affect yield. The superior traits had by F2 plants can be observed in subsequent generations, thus providing a valuable genetic resource for breeding programs and certain genomic studies.